Mathematics Courseware for Autism children - Ahmad, I. (2010)
Children with autism are socially impaired and usually having problem with verbal and non-verbal communication. The concept of Behaviorism learning theory is seen as an innovative pedagogy to be uses in producing mathematics (Numbers) courseware for autism children. Behaviorism learning theory is focuses on a behavioral pattern being repeated until it becomes automatic. The concepts of ‘Drill and Practices’ is chosen in developing the Mathematics courseware to learn number. This prototype is specially developed for moderate level of autistic children targeted for primary schools which covered syllabus of Mathematics Component in the Huraian Kurikulum Pendidikan Khas Bermasalah Pembelajaran (PKBP) set by Ministry of Education. In our research, Behaviorism learning theory and multimedia technology has been blended in enhancing learning performance among autistic child. Moreover, very little empirical research has been conducted to integrate Behaviorism learning theory into learning courseware for autistic learners. Testing and evaluations has been made with autistic children and teachers from primary school in Ujong Pasir , Melaka and Autism Intervention Centre (NASOM). We aims to share the positive feedback from the tester and the possibility to commercialized the research project